Algorithmic Research and Application Using the Rayleigh Method - Anghel Drugarin Cornelia Victoria; M. Ayaz Ahmad; N. Ameer Ahamad; Lyashenko, V. (www.ijsr.net, 2015)
The aim ofthis article is topresent the general notions and algorithm about power (Rayleigh) method. The solutions for a numerical example are given and the C++ program illustrated the facility ofthis method. Wecan concluded, that the small number of iterations resulted todetermined the equation solutions, indicated us, that the chosen ofpower method isa good decision.
Keywords: Matrixes; Rayleigh numerical method; algorithm; power method; research; DevC++ program